The Efficacy and Late Toxicities of Computed Tomography-based Brachytherapy with Intracavitary and Interstitial Technique in Advanced Cervical Cancer - Dang, Yun-Zhi (J Cancer, 2018)
Purpose: To report the efficacy and late side effects(LSEs) of CT-based image-guided brachytherapy for the treatment of cervical cancer. Materials: Between 2008 and 2014, 100 patients with FIGO stage IIB-IVA cervical carcinoma were analyzed. The patients received pelvic irradiation (45-50 Gy in 25 fractions) with concurrent chemotherapy, whereas the mean prescribed EBRT dose, including initial and boost doses to positive lymph nodes, ranged from 54 to 64 Gy. Afterwards, intracavitary(IC) or combined intracavitary/interstitial(IC/IS) brachytherapy was performed using a CT-based procedure with prescribed doses of 6 or 8 Gy in 3-7 fractions. Results: The median follow-up time was 46 months. The 5-year local control, distant metastasis-free survival, and overall survival rates were 88.9%, 81.8%, 77.9%, respectively. IC/IS brachytherapy improved the HR-CTV D90 compared with IC (p<0.01). Seven patients (7.0%) had grade 2 bladder LSEs and none had grade 3/4 bladder LSEs. There was no significant relationship between bladder LSEs and the dose-volume histogram (p>0.05 for all). Thirty-seven patients (37%) had grade 2 rectal LSEs, 3(3%) had grade 3 rectal LSE. The rectum D(1cc), D(2cc), and D(5cc) values were significantly higher in patients with grades 2/3 rectal toxicity than in those with grades 0/1 (p<0.05 for all). There was no grade 2 and above small bowel LSEs. Conclusions: CT-based brachytherapy planning can achieve excellent local control with acceptable morbidity. HR-CTV D90 can increase in the IC/IS group compared with the IC group. The D(1cc), D(2cc), and D(5cc) all showed excellent predictive values for rectal LSEs.